Factors related to adherence to treatment for systemic hypertension - Fava, Silvana Maria Coelho Leite (2014)
This study aimed to seek the evidence available in the literature regarding the factors related to adherence to treatment for systemic hypertension. It used the method of integrative review in the databases MEDLINE, CINAHL, and LILACS, using the keywords: hypertension, compliance, non-compliance, adherence, non-adherence, patient compliance, in the period 2004 – 2008, and articles in Portuguese, English and Spanish, with the use of a validated instrument and content analysis. 28 studies were selected, 64.3% of which had level of evidence VI. The following were identified as factors related to adherence to treatment: treatment costs, educational activities, sex, physician-patient relationship, physiological and behavioral aspects, drug therapy, attending checkups and lifestyle. The use of combined strategies is suggested in order to increase the individuals’ adherence to the treatment. Gaps point to the valorization of dialogic relationships for integrated and more efficacious health practices